Bevacizumab plus chemotherapy as salvage treatment in chemorefractory patients with metastatic colorectal cancer - Geva, Ravit (Dove Medical Press, 2013)
PURPOSE: The combination of chemotherapy and bevacizumab, a monoclonal antibody targeting the vascular endothelial growth factor, is consistently being used as first- and second-line treatment in patients with metastatic colorectal cancer (mCRC). There is little data of the activity of bevacizumab in chemorefractory mCRC patients. The aim of this retrospective single center study was to evaluate the activity of bevacizumab combined with chemotherapy in this study population. METHODS: Forty-six consecutive mCRC patients treated in the University Hospital Gasthuisberg (Leuven, Belgium) receiving bevacizumab in advanced lines following failure of conventional chemotherapy were included in this study. Treatment regimen consisted of bevacizumab 5 mg/kg in combination with leucovorin, 5-fluorouracil, and oxaliplatin (FOLFOX) or leucovorin, 5-fluorouracil, and irinotecan (FOLFIRI). RESULTS: Bevacizumab plus chemotherapy was used in third-line treatment in eight (17%) patients and in fourth-line treatment or more in 38 patients (83%). All patients previously failed irinotecan-based chemotherapy, 44 (96%) failed oxaliplatin-based regimens, and 40 (87%) failed treatment with cetuximab. Bevacizumab was given in combination with irinotecan-based chemotherapy in 36 patients, oxaliplatin-based chemotherapy in nine patients, and with single agent 5-fluorouracil in one patient. Objective response was demonstrated in ten patients (22%) and disease control in 38 (83%) with a median progression-free survival of 8.9 months and a median overall survival of 13.8 months. Only four patients experienced grade III and above bevacizumab-related toxicity. CONCLUSION: Taking into account the retrospective nature of the study which can influence the selection of patients, bevacizumab given in advanced lines after failure of conventional chemotherapy and antiepidermal growth factor receptor agents can result in high disease control rates in patients with mCRC.